2019
DOI: 10.2196/11939
|View full text |Cite
|
Sign up to set email alerts
|

Technical Support by Smart Glasses During a Mass Casualty Incident: A Randomized Controlled Simulation Trial on Technically Assisted Triage and Telemedical App Use in Disaster Medicine

Abstract: Background To treat many patients despite lacking personnel resources, triage is important in disaster medicine. Various triage algorithms help but often are used incorrectly or not at all. One potential problem-solving approach is to support triage with Smart Glasses. Objective In this study, augmented reality was used to display a triage algorithm and telemedicine assistance was enabled to compare the duration and quality of triage with a conventional one. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…Follmann et al compared traditional triaging during a simulated mass casualty event to the use of Smart Glasses through both an interactive triage algorithm app and telemedical support. The study found that while traditional triaging was faster, triaging using both an interactive Smart Glasses app and a physician with triage experience available by telemedicine was significantly more accurate [25].…”
Section: Resultsmentioning
confidence: 99%
“…Follmann et al compared traditional triaging during a simulated mass casualty event to the use of Smart Glasses through both an interactive triage algorithm app and telemedical support. The study found that while traditional triaging was faster, triaging using both an interactive Smart Glasses app and a physician with triage experience available by telemedicine was significantly more accurate [25].…”
Section: Resultsmentioning
confidence: 99%
“…We sought to investigate this subject in a small preliminary field experiment (Figure 1B, C and D) in which the results were promising. Similarly, Follmann et al examined AR telementoring support in a simulated mass casualty event and showed that triage with telementoring was slower, but significantly more accurate,20 and Carenzo et al found that AR telementoring made disaster triage more efficient 21…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons senior physicians and surgeons are recommended (and found to perform better 6,75 ) over other less highly trained or experienced providers. First, there is some evidence that their knowledge and understanding of triage may be better, 6 but that seems to be a minor component.…”
Section: Who Should Conduct Triage?mentioning
confidence: 99%